Analisis Kemampuan Berpikir Kreatif pada Konsep Polimer dengan Pendekatan STEAM Bermuatan ESD Siswa SMA Negeri 1 Bantarbolang - Siti Nurfadilah; Joko Siswanto (Media Penelitian Pendidikan : Jurnal Penelitian dalam Bidang Pendidikan dan Pengajaran, 2020)
STEAM learning arises in response to the need to enhance students' interests and skills in the fields of Science, Technology, Engineering, and Mathematics (STEM). STEAM combines "arts" with STEM learning for the purpose of increasing student involvement, creativity, innovation, problem solving skills, and other cognitive benefits, and to improve work skills (eg teamwork, communication, adaptability) necessary for career and economic progress. Education for Sustainable Development (ESD) is Education for Sustainable Development empowering students to take responsible decisions and actions for environmental integrity, fair economic and community viability, for present and future generations, while respecting cultural diversity. STEAM learning with ESD is expected upgrade student creativity so that student can to finish the problem without sacrifice environment. The purpose of this research study is to find out the students' creative thinking abilities on the concept of polymers by using STEAM Approuch with ESD. The subjects of the research were students of class XII MIPA 4 of SMA Negeri 1 Bantarbolang. The preliminary study was conducted in the 2019/2020 semester 2 academic year. The data used the creative thinking ability test method and the creative attitude questionnaire sheet. After being collected it was analyzed and it was found that the achievement of creative thinking abilities of students amounted to 29.19 (36.5%) while the attainment of students' creative attitudes was 54.53 (74.65%).